PELAKSANAAN PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSIF - KHOTIMAH, KHUSNUL (Jurnal Pendidikan Khusus, 2017)
ABSTRACT An inclusive school was a school joining special need learners and regular learners in one class. The education service given was also suitable with each students’ needs. The purposes of this research were to describe the implementation (planning, implementing, and evaluation), to describe the problem factors and the solution dealing with the implementation, educators, media and infrastructure supporting in learning adaptive physical education for special need learners in inclusive school. This research used the method of qualitative research with descriptive kind.Based on the data analysis it was obtained that the implementation of learning adaptive physical education for special need learners in inclusive school had already been implemented well. The modification done to special need learners was to the learning and the learning activity. The special need learners could wholly follow the learning because it was found easy. The condition of the learners who were less active in following the learning implementation, accompanying which was not done to every class, the media used was the same with the regular learners and less sufficient infrastructure made the teachers and GPK try as good as possible in order that the learning could run smoothly and utilized the media and infrastucture which had been existed by matching according to the special need learners’ ability. The exact learning method was suitable with the learners’ ability and characteristics and did accompanying when the learning was performing and the suitable media and infrastructure would help the teachers very much in establishing the program of adaptive sport education in inclusive school. Keywords: Inclusive school, adaptive physical education, special need learners